Pulmonary Function of Tuberculosis Patients in Medication at Dr. Hasan Sadikin General Hospital Bandung 2013–2014 - Shalahuddin Galih Pradipta; Hendarsyah Suryadinata; Setiawan Setiawan (Althea Medical Journal, 2017)
Background: Tuberculosis (TB) is a dangerous global disease that already affects millions of people in the world and acts as the second most frequent cause of death in infectious diseases. Tuberculosis mostly attacks the lung and the inflammation process causes lung damage. The lung damage causes a decrease in pulmonary function. There has been no study about tuberculosis patient lung function in the advanced stage of medication.Methods: This study was conducted from August–October 2014 at DOTS Policlinic of Dr. Hasan Sadikin General Hospital Bandung. The study population was lung TB patients. The inclusion criteria were 1st category lung TB patients with anti-TB drug treatment on intensive phase. The exclusion criteria were extrapulmonary TB patients, patients with lung surgery history, and patients with asthma or chronic obstructive pulmonary disease (COPD). This study used purposive sampling. The subjects were given a spirometry test where the forced expiratory volume 1 second (FEV1), forced vital capacity (FVC), and their ratio were collected and then interpreted.Results: Among the 60 subjects included in this study, the data showed that 83.4% of the subjects had a decreased pulmonary function consisting of obstructive (6.7%) and restrictive patterns (76.7%).Conclusions: The majority of pulmonary TB patients treated with 1st category anti-TB drugs during intensive phase have a decrease in pulmonary function and most of them have restrictive pattern of pulmonary function.